A basic analogue of FoxÂ´s H-function - Saxena, R. K.; Modi, G. C.; Kalla, S. L. (Revista Técnica da Faculdade de Engenharia da de Zulia, 2011)
Certain basic integrals and integral representations for a basic analogue of FoxÂ´s H-function are investigated in this paper.